The Effect of Increasing Vehicle Volume on Some Roads in Surabaya Post Pandemic - Ibnu Sholichin; Achmad Dzulfiqar Alfiansyah (Journal of Civil Engineering Science and Technology (CI-TECH), 2022)
Population growth and economic development in Indonesia affect the increase in the volume of vehicles. In the era of the pandemic, Indonesia's population growth has increased, so the need for vehicles also increases. The increase in the volume of vehicles, causes congestion in various areas. The WFH (Work From Home) policy, due to the Covid-19 pandemic, has reduced the use of vehicles in traffic. Two years after the pandemic, in 2022, the volume of vehicles in traffic will be higher due to activities that have started to return to normal. The abolition of the WFH (Work From Home) policy has resulted in school offices, tourist attractions, and other infrastructure making the activities of the Indonesian people and economy rise slowly. Although the economy in Indonesia has not increased significantly or can be called unstable, the purchasing power of motorized vehicles has increased. From the results of the research carried out above, it is known that the capacity of Darmo road and Pemuda road has increased the DS value (degree of saturation) in the post-pandemic period compared to the pandemic conditions during the PSBB period. The increasing community activities caused the increased DS value (degree of saturation). This resulted in traffic on Jalan Darmo, Pemuda, and Ahmad Yani becoming more congested than during the pandemic.